2019
DOI: 10.22207/jpam.13.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of the Antioxidative Properties of Chickpea Beverages Through Fermentation Carried Out by Probiotic Strain Lactobacillus plantarum 299v

Abstract: The purpose of the research was to obtain different variants of chickpea beverages and subject them to probiotic fermentation carried out by Lactobacillus plantarum 299v in order to compare properties of received products. The study focused on the influence of the fermentation process on changes in protein profiles, antioxidative properties, pH values, and reducing power (RP). The analyzed variants of chickpea beverages exhibited diversity in terms of RP. Fermented products were characterized by significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…On the contrary, fermentation with LAB appears to be an attractive processing alternative for improving the nutraceutical and sensorial quality of legumes (Curiel et al, 2015; Di Pasquale et al, 2020; Gobbetti et al, 2019). Fermented chickpea has been used for obtaining health‐enhancing ingredients for novel functional foods such as gluten free baked goods and ready‐to‐eat/drink products (Skrzypczak et al, 2019; Xiao et al, 2016). In Western countries, LAB are preferred over fungi for improving the quality of pulses by fermentation, but the right selection of microorganisms is a crucial step.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, fermentation with LAB appears to be an attractive processing alternative for improving the nutraceutical and sensorial quality of legumes (Curiel et al, 2015; Di Pasquale et al, 2020; Gobbetti et al, 2019). Fermented chickpea has been used for obtaining health‐enhancing ingredients for novel functional foods such as gluten free baked goods and ready‐to‐eat/drink products (Skrzypczak et al, 2019; Xiao et al, 2016). In Western countries, LAB are preferred over fungi for improving the quality of pulses by fermentation, but the right selection of microorganisms is a crucial step.…”
Section: Discussionmentioning
confidence: 99%
“…As result, the researches on novel applications and the development of legumes derived products have significantly raised in the last years. In this regard, chickpea flour has been used for the formulation/supplementation of a wide variety of products such as pasta, bakery products, snacks, yogurts and beverages that could be consumed by celiac disease patients due to its gluten‐free nature (Hussein et al, 2020; Skrzypczak et al, 2019; Xiao et al, 2016; Yagci & Evci, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A chickpea-based beverage fermented with Lactiplantibacillus plantarum subsp. plantarum has been demonstrated to have higher reducing power, and reduced content of β-conglycinin and glycinin, which are considered to be food allergens [225].…”
Section: Fermentation Of Legume-based Beverages Using Labmentioning
confidence: 99%
“…In the first session, five samples were delivered, and in the second, 4. All participants involved in the evaluation were thoroughly informed about the manufacturing process and the sensory attributes of the product 21,26 .…”
Section: Overall Acceptabilitymentioning
confidence: 99%
“…The best formulation of a fermented beverage based on soybeans and chickpea reported by Wang et al 21 had 6.20 points on a 9-point scale. Skrzypczak et al 26 reported a 6.80-point on a 9-point scale in a chickpea beverage; Freire et al 37 reported a 5.17-point on a 9-point scale in a cassava and rice-based beverages fermented, Da Silva et al 38 found values of 8-point on a 9-point scale in a drinkable soy kefir-based functional beverage and Caluza 39 obtained between 6-7 points on a 9-point scale in a fruity flavored drinkable soy.…”
Section: Overall Acceptabilitymentioning
confidence: 99%